VWA domain of S5a restricts the ability to bind ubiquitin and Ubl to the 26S proteasome - Piterman, Ravit (Mol Biol Cell, 2014)
The 26S proteasome recognizes a vast number of ubiquitin-dependent degradation signals linked to various substrates. This recognition is mediated mainly by the stoichiometric proteasomal resident ubiquitin receptors S5a and Rpn13, which harbor ubiquitin-binding domains. Regulatory steps in substrate binding, processing, and subsequent downstream proteolytic events by these receptors are poorly understood. Here we demonstrate that mammalian S5a is present in proteasome-bound and free states. S5a is required for efficient proteasomal degradation of polyubiquitinated substrates and the recruitment of ubiquitin-like (Ubl) harboring proteins; however, S5a-mediated ubiquitin and Ubl binding occurs only on the proteasome itself. We identify the VWA domain of S5a as a domain that limits ubiquitin and Ubl binding to occur only upon proteasomal association. Multiubiquitination events within the VWA domain can further regulate S5a association. Our results provide a molecular explanation to how ubiquitin and Ubl binding to S5a is restricted to the 26S proteasome.